New species group and four new species of Brueelia Kéler, 1936 (Phthiraptera: Ischnocera) from African buntings (Passeriformes: Emberizidae) - Daniel R. Gustafsson; Sarah E. Bush (European Journal of Taxonomy, 2025)
Four new species of Brueelia Kéler, 1936, are described from African emberizids: Brueelia anomala sp. nov. from Emberiza striolata striolata (Lichtenstein, 1823); Brueelia kalaharicae sp. nov. from Emberiza flaviventris kalaharica Roberts, 1932; Brueelia saharae sp. nov. from Emberiza sahari Levaillant, 1850; Brueelia semicingulata sp. nov. from Emberiza tahapisi arabica (Lorenz von Liburnau & Hellmayr, 1902). All four species belong to a new species group within Brueelia, here termed the ‘Brueelia anomala species group’, characterized by the presence of a transverse dorsal preantennal suture that does not reach the lateral margins of the head; in three of the four species the gonopore is also modified in a way that is previously unknown within Brueelia.